Gentiana scabra Restrains Hepatic Pro-Inflammatory Macrophages to Ameliorate Non-Alcoholic Fatty Liver Disease - Zheng, Yiyuan; Fang, Dan; Huang, Chaoyuan; Zhao, Lina; Gan, Liming; Chen, Youlan; Liu, Fengbin (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) has become a progressive metabolic disease that is emerging as a global epidemic. Given the complex pathogenesis has not been fully elucidated, barely specific pharmacological therapy is recommended in current guidelines. Gentiana scabra (GS) is a commonly used herb in Tibetan medicine, which has received much attention in recent years due to its diverse pharmacological properties, including anti-inflammation, anti-oxidation, and anti-fibrosis. However, the therapeutic mechanisms are still unclear. Our investigation demonstrated a regulatory effect of GS on pro-inflammatory macrophages, which was extensively investigated in NAFLD that revealed intimate participation in the disease evolution, and the non-canonical IKK family member TANK-binding kinase 1 (TBK1) was involved in this process. Plasmid vectors for shTBK1 and amlexanox (AML), an inhibitor of TBK1, were used in this study to verify the mechanisms of TBK1 both in vitro and in vivo, while a co-culture system for hepatocytes and BMDMs was constructed to confirm the critical role of macrophages for inflammatory cascade. The results revealed that metabolic burden up-regulated the phosphorylation of TBK1, resulting in activation of NF-κB signaling pathway, and consequently caused an elevated expression of MCP1 to induce the macrophage recruitment and accelerate the inflammatory cascade. In contrast, GS could inhibit the TBK1 phosphorylation and the MCP1 expression to restrain the recruitment of pro-inflammatory macrophages, so as to provide curative effects on metabolic dysfunction and inflammation. Considering that GS is non-toxic and can be used as a kind of tea for long-term drinking, we propose it may be an effective option for the prevention and treatment of NAFLD, which deserves further exploration and application, and may provide new insights to improve the current standardized intervention strategy.